SERAPAN FOSFOR OLEH TANAMAN JAGUNG PADA APLIKASI TEPUNG TULANG AYAM DAN BAHAN ORGANIK DI TANAH LATOSOL - Peniwiratri, Lelanti; Ratih, Yanisworo Wijaya (Fakultas Pertanian, Universitas Janabadra, 2024)
This study aims to determine the effect of chicken bone meal and organic materials on the absorption of P by corn plants grown in Latosol soil. The study used a two-factor Completely Randomized Design (CRD). The first factor, the dosage of chicken bone meal consists of 4 levels: without chicken bone meal (T0), chicken bone meal 2% (T1), 4% (T2), 6% (T3) of the weight of organic material. The second factor, the type of organic material consists of 3 levels: without organic material (B0), compost 3% of the weight of the soil (B1) and manure 3% of the weight of the soil (B2). Each treatment was repeated 3 times. The results showed that chicken bone meal and organic material fertilizers had a significant effect on increasing the available P of Latosol soil and P absorption by corn plants. The provision of chicken bone meal fertilizer 4% of the weight of organic material and compost 3% of the weight of the soil was the best result for increasing the availability of P in Latosol soil and P absorption in corn.